THE INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY AND PRICE PERCEPTION ON THE COMPETITIVENESS OF ORIFLAME PRODUCTS IN JAKARTA - Rika Indriani; Suadi Sapta Putra; Kumba Digdowiseiso (SEAN Institute, 2023)
This research aims to determine the influence of brand image, product quality and price perception on the competitiveness of Oriflamme products in Jakarta. The sample in this study was 100 respondents who had used Oriflame products. This research uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) Version 23 program. The results of multiple linear regression analysis show that the brand image variable (X1) has an influence of 0.154 or 15.4%, The product quality variable (X2) has an influence of 0.142 or 14.2%, the price perception variable (X3) has an influence of 0.316 or 31.6% on competitiveness. Thus, it can be concluded that brand image variables, product quality variables and price perceptions influence product competitiveness together.